Birthing, Nativity, and Maternal Depression: Australia and the United States1, 2. Issue 3 (September 2016) - Martinson, Melissa L.; Tienda, Marta
This study analyzes two birth cohort surveys, the Longitudinal Study of Australian Children and Early Childhood Longitudinal Study, to examine variation in maternal depression by nativity, duration of residence, age at migration, and English proficiency in Australia and the United States. Both countries have long immigrant traditions and a common language. The results demonstrate that US immigrant mothers are significantly less depressed than native-born mothers, but maternal depression does not differ by nativity in Australia. Moreover, the association between duration of residence and maternal depression is not linear: Recent arrivals and long-term residents exhibit the highest depression levels. Lack of English proficiency exacerbates maternal depression in Australia, but protects against depression in the United States. Differences in immigration regimes and welfare systems likely contribute to the differing salience of nativity for maternal depression.